2020
DOI: 10.4317/jced.56500
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of bioactive cements on biomimetic remineralization of dentin

Abstract: Background: This study was designed to quantitatively compare the presence of apatite peaks on demineralized dentin to induced bio-mimetically by bioactive commercial materials. Material and Methods: Dentin slice specimens (n=6) were prepared and demineralized by by17% EDTA for 2 hours. Each disks materials (Theracal, Biodentine, CPP-ACP) were freshly prepared and was maintained in close contact with a demineralized dentin specimen immersed in PBS solution during one week. To evaluation of bioactivity, cements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…The result revealed that the bioactive cements and CPP-ACP had bioactivity capability for one week [8] . TheraCal LC and Activa exhibited a low degree of conversion, low calcium ion release, acceptable biocompatibility and moderate antibacterial activity [9] .…”
Section: Biocompatibility and Cytotoxicity 311 Theracalmentioning
confidence: 97%
“…The result revealed that the bioactive cements and CPP-ACP had bioactivity capability for one week [8] . TheraCal LC and Activa exhibited a low degree of conversion, low calcium ion release, acceptable biocompatibility and moderate antibacterial activity [9] .…”
Section: Biocompatibility and Cytotoxicity 311 Theracalmentioning
confidence: 97%
“…Demineralization of enamel is the first sign of white spot lesion and progression of mineral loss and disintegration by acids lead to dentin involvement. Various agents with different forms to overcome the demineralization challenge (2) .…”
Section: Introductionmentioning
confidence: 99%
“…This procedure is performed aiming to be enhanced by the use of ion-releasing cavity liners [6]. The key to success in this approach is to use remineralizing agents during indirect pulp capping [7]. Dentin remineralization is more complex than enamel remineralization due to the presence of higher amounts of organic matrix [7].…”
Section: Introductionmentioning
confidence: 99%
“…The key to success in this approach is to use remineralizing agents during indirect pulp capping [7]. Dentin remineralization is more complex than enamel remineralization due to the presence of higher amounts of organic matrix [7]. The remineralization process occurs by the growth of the remaining hydroxyapatite crystals in the affected dentin [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation